Performance comparison of grid-faulty control schemes for inverter-based industrial microgrids - Camacho A. (2017)
Several control schemes specifically designed to operate inverter-based industrial microgrids during voltage sags have been recently proposed. This paper first classifies these control schemes in three categories and then performs a comparative analysis of them. Representative control schemes of each category are selected, described and used to identify the main features and performance of the considered category. The comparison is based on the evaluation of several indexes, which measure the power quality of the installation and utility grid during voltage sags, including voltage regulation, reactive current injection and transient response. The paper includes selected simulation results from a 500 kVA industrial microgrid to validate the expected features of the considered control schemes. Finally, in view of the obtained results, the paper proposes an alternative solution to cope with voltage sags, which includes the use of a static compensator in parallel with the microgrid. The novelty of this proposal is the suitable selection of the control schemes for both the microgrid and the static compensator. The superior performance of the proposal is confirmed by the analysis of the quality indexes. Its practical limitations are also revealed, showing that the topic studied in this paper is still open for further research.